On the Determinants of Terrorism Risk Concern in Europe - Konstantinos Drakos; Cathérine Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We investigate whether differences in terrorism risk are mirrored on terrorism risk concern across European countries for the period 2003-2007. We find that the average propensity for terrorism risk concern is indeed affected by actual risk levels. Furthermore, country and individual heterogeneity contribute substantially to the variation of observed risk concern. According to our findings, males, singles and individuals with white collar jobs are less likely to mention terrorism as one of the most pressing issues their country faces. In contrast, political positioning towards the right end of the spectrum and living in rural areas make it more likely to be concerned about terrorism. As far as competing risks are concerned, we find that the likelihood terrorism is mentioned increases when competing risks' drivers also increase such as taxation, inflation, unemployment and poverty risk at work. In contrast, terrorism is less likely to be mentioned when the determinants of crime, immigration rates, housing costs and pensions are higher. Finally, based on the Bayesian framework we also examine the formation of terrorism risk perceptions, and decompose the observed country level time series of terrorism activity into a long and a short run component. We conclude that the observed risk concern variation is mostly explained by the trend part of terrorism activity countries face, although cyclical variations are also important.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330; probit; survey data; terrorism risk concern; time series decomposition